(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
There are many secrets and principles of language and speech. Language and speech together are a subject of common use. All their principles are equally important, because in the relationship between language and speech, neuropsycholinguistics also answers. There is always something new in this field of science. Cognitive principles—the brain and its relationship to language—are important in language acquisition and categorization. Although this work is very complicated and difficult, a person can be healed with a kind word. Because the word is also a source of energy in managing the mind. This is one of the practically unsolved problems of neuropsicholinguistics. The brain is a mysterious world, if it is studied from the point of view of the influence of speech, how we perceive language, how we talk becomes easier. A smile also relaxes the human brain. It nourishes the human psyche and renews its spiritual world. A smile is a very delicate matter, it is necessary to know its place and learn ways to give it to someone.